Application of Business Model Canvas as a Business Strategy in Creative Economy Businesses in The Field of Photography in Makassar City - Annisa Paramaswary Aslam (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This research aims to find out how the application of the canvas business model has been carried out by creative economy business actors in the field of photography and provide alternative strategy options to develop their business. This research is descriptive research with a qualitative approach, data collection techniques are carried out using observation, interview, and documentation methods. The results of this study indicate that the business run by creative economic businesses in the field of photography is part of a business model canvas consisting of 9 blocks where the results of the SWOT analysis that has been carried out, there are four strategic options for creative economic businesses in the field of photography consisting of strengths opportunities (SO), weakness opportunities (WO), strength threats (ST), and weakness threats (WT). Of the four strategy options, the right strategy to be developed in the creative economy business in photography is weakness opportunities (WO). From the results of the mapping that has been carried out by researchers using the business model canvas and alternative strategies, researchers assess that businesses that have been running can apply the business model canvas as an alternative business model and the strategies that have been given by researchers can be implemented by creative economic businesses in the field of photography to increase business income.